"Digitale Souveränität": Kontextualisierung des Phänomens in der Domäne der medial vermittelten öffentlichen Kommunikation unter besonderer Berücksichtigung von Reader Analytics - Svenja Hagenhoff (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Buchwissenschaft, Professur für Buchwissenschaft, insb. E-Publishing und Digitale Märkte, 2020)
– The term 'digital sovereignty' is increasingly used in the context of the discussion about 'digital transformation'. Sovereignty in the digital world is considered a prerequisite for being able to help shape the digital transformation in all functional areas of society. However, the term 'digital sovereignty' has so far been used primarily in a prescriptive-normative sense; a differentiated theoretical work and concrete contextualizations for different social functional areas are still a desideratum. This working paper therefore sets itself the task of contextualizing the idea of digital sovereignty in the domain of public communication mediated by the media: The question arises where exactly sovereignty as a specific object of investigation in media society and media communication plays a role. This requires a conceptual-abstract version that goes beyond the mere enumeration of obvious phenomena or normatively influenced demands ('freedom of opinion', 'informational self-determination').
urn:nbn:de:bvb:29-opus4-150157
Keywords: 000; Informationsfreiheit; Lesen; Medienökonomie; Reader Analytics; Souveränität